ECONOMIC IMPACT OF INSTITUTING SMOKING PROHIBITIONS IN NEW YORK CITY (Tufts Archival Research Center, 2007)
New York State Association of Tobacco and Candy Distributors report on the economic impact of instituting smoking prohibitions in New York City. Discusses the impact it would have on individuals, the economic impact it would have on affected public places, and the overall impact on New York City. Adresses inequities in smoking legislation and its disproportionate impacts on low and moderate income working people. Finds businesses and the city itself will suffer financially.